Kainate receptors and synaptic plasticity. (15th September 2021) - Nair, Jithin D.; Wilkinson, Kevin A.; Henley, Jeremy M.; Mellor, Jack R.
Abstract: Synaptic plasticity has classically been characterized to involve the NMDA and AMPA subtypes of glutamate receptors, with NMDA receptors providing the key trigger for the induction of long-term plasticity leading to changes in AMPA receptor expression. Here we review the more subtle roles played by kainate receptors, which contribute critical postsynaptic signalling as well as playing major presynaptic auto-receptor roles. We focus on two research areas: plasticity of kainate receptors themselves and the contribution they make to the plasticity of synaptic transmission. This article is part of the special issue on Glutamate Receptors - Kainate receptors. Highlights: Synaptic kainate receptor expression is adaptable and plastic. Kainate receptors regulate presynaptic release of neurotransmitter. Kainate receptors can control expression of other glutamate receptors at synapses. Kainate receptors can signal by canonical ionotropic or non-canonical metabotropic mechanisms.